2023
DOI: 10.3390/aerospace10030233
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification of Imperfect Diagnostics

Abstract: The operable state of a system is maintained during operation, which requires knowledge of the system’s state. Technical diagnostics, as a process of accurately obtaining information about the system state, becomes a crucial stage in the life cycle of any system. The study deals with the relevant problem of uncertainty quantification of imperfect diagnostics. We considered the most general case when the object of diagnostics, the diagnostic tool, and the human operator can each be in one of the many states. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In 1987, ref. [94] (also referenced in [27]) proposed a maintenance model featuring a sequential inspection schedule. The inspection policies are considered for both finite and infinite time horizons.…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
See 3 more Smart Citations
“…In 1987, ref. [94] (also referenced in [27]) proposed a maintenance model featuring a sequential inspection schedule. The inspection policies are considered for both finite and infinite time horizons.…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
“…Considering Equation (120), the equations for conditional probabilities-Equations ( 112)-(115)-are significantly simplified in [94] and [27] (p. 89):…”
Section: Models With Non-constant Probabilities Of Correct and Incorr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies [53,54] have shown that the probabilities of imperfect inspections at condition-based and predictive maintenance are functions of the degradation model parameters and strongly depend on time. In the study [55], the case of imperfect testing of the crack depth in a fighter wing was considered. The study showed that flight hours have a significant impact on the probabilities of a false positive and a false negative.…”
Section: Literature Reviewmentioning
confidence: 99%